2012
DOI: 10.1136/archdischild-2012-303020
|View full text |Cite
|
Sign up to set email alerts
|

Congenital diaphragmatic hernia with(out) ECMO: impaired development at 8 years

Abstract: Children with CDH-whether or not treated with neonatal ECMO-are at risk for long-term morbidity especially in the areas of motor function and concentration. Despite their impairment, children with CDH have a well-developed feeling of self-competence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
75
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 62 publications
(84 citation statements)
references
References 31 publications
5
75
3
Order By: Relevance
“…31 Normal or even better perceived feelings of self-worth are not unusual; this has also been reported in children with congenital heart disease 32 and in CDH patients, whether or not treated with neonatal ECMO. 14 We showed that CDH patients were satisfied with their motor performance and had normal feelings of self-worth despite a higher proportion of actual motor function problems compared with the ECMO survivors without CDH.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…31 Normal or even better perceived feelings of self-worth are not unusual; this has also been reported in children with congenital heart disease 32 and in CDH patients, whether or not treated with neonatal ECMO. 14 We showed that CDH patients were satisfied with their motor performance and had normal feelings of self-worth despite a higher proportion of actual motor function problems compared with the ECMO survivors without CDH.…”
Section: Discussionmentioning
confidence: 71%
“…On the basis of previous studies on motor impairments in neonatal ECMO survivors, 3,[6][7][8]10,14,18,19 we hypothesized that these children are likely to have low perceptions of competence in the physical domain because of repeated experiences of poor movement skills with loss of interest in the motor domain and avoidance of motor activities, due to fear of failure and peer criticism. It is conceivable that this may reduce opportunities to practice skills and participate socially and hence result in impaired HRQoL.…”
Section: Doimentioning
confidence: 99%
See 1 more Smart Citation
“…This confirms our earlier observations in 35 eightyear-old CDH survivors who had longterm problems with motor function and concentration, even when they had not been treated with ECMO. 21 A high presence of CLD and increased airflow obstruction that deteriorates over time 22 may contribute to poor motor function performance in these CDH patients.…”
Section: Discussionmentioning
confidence: 99%
“…15 Both tests assess verbal and nonverbal intelligence, have been shown to have good reliability and validity, 14,15 and have been used interchangeably by our group in previous research. 16 For all 4 tests, a normalized population mean ± SD IQ score of 100 ± 15 is used. 13 -15 The outcome on all 4 tests is referred to as intelligence or IQ.…”
Section: Intelligencementioning
confidence: 99%